An Analytical Study on global radiation and meteorological parameters for India. Issue 10 (23rd August 2020) - Mahima; Karakoti, Indira; Nandan, Hemwati; Pathak, P. P.
ABSTRACT: A study is carried out for global radiation (global horizontal and global tilted radiation) and meteorological parameters (humidity and temperature) recorded for a period of one year (2011) at the National Institute of Solar Energy (NISE), Gwal Pahri (28.42 ° N, 77.15 ° E), India. Maximum global horizontal radiation of 7.22 kWh/m 2 is recorded in the month of June while minimum of 0.91 kWh/m 2 is observed in February. The highest value of the tilted radiation 7.27 kWh/m 2 is recorded in March and the lowest value 0.90 kWh/m 2 is noticed in February. The maximum temperature of 36.5°C and humidity of 87.6% are observed in the months of June and July, respectively. Conversely, minimum temperature of 6.1°C and humidity 21.7% are noticed in the months of January and April, respectively. Furthermore, meteorological parameters have been correlated with global radiation on horizontal and tilted surface. The study is vital for the performance analysis of different solar energy applications .